Дифференциальные включения с производной Хукухары - Комлева, Т.А.; Плотников, А.В. (Інститут математики НАН України, 2007)
Введено два типи диференціальних включень з похідною Хукухари і розглянуто їх властивості. Для диференціального включення другого типу наведено різні означення розв'язку та доведено теореми існування звичайного розв'язку і компактність їх множини. We introduce two types of differential inclusions with Hukuhara derivative and consider properties of such inclusions. For differential inclusions of the second type, we give several definitions of a solution, and prove theorems on existence of an ordinary solution and establish compactness of the set these solutions.